Iron mediated oxidative ring opening-homocoupling of cyclopropanols: facile access to 1,6-diketones - Shinde, Ravi A.; Shirsath, Sachin; Muthukrishnan, M. (ChemistrySelect, 2025)
We have developed a new approach for the synthesis of 1,6-diketones via iron-catalyzed ring opening of cyclopropanol with a nontoxic, inexpensive iron catalyst under open-air conditions. This method eliminates the need for additives and employs tert-butanol as an eco-friendly solvent. This methodology allows rapid access to a variety of symmetrical 1,6-diketones under mild conditions. Preliminary mechanistic studies revealed the involvement of radical pathways.
Keywords: 1; 6-Diketone synthesis; C & horbar; C bond cleavage; cyclopropanols; Homocoupling; Iron mediated